Synchronous reluctance motor iron losses: considering machine non-linearity at MTPA, FW, and MTPV operating conditions - Mahmoud, Hanafy; Bacco, Giacomo; Degano, Michele; Bianchi, Nicola; Gerada, C. (IEEE, 2018)
Synchronous reluctance machine has high flux density fluctuations in the iron due to the high harmonics results from the rotor anisotropy. Thus, an accurate computation of the iron losses is of paramount importance, especially during the design stage. In this paper, a non-linear analytical model considering the magnetic iron saturation and the slotting effect is proposed. The model estimates accurately the iron losses at a wide range of operating speed. In addition, the accuracy of the non-linear model when the machine is highly saturated, i.e. when it works along the MTPA trajectory, is presented and verified. The model presented is general and can be applied to other configurations. A 36-slot four-pole machine, with three flux-barriers per pole is considered as a case study. Finite element analysis is used to validate the results achieved by means of the non-linear analytical model. Furthermore, an experimental setup is built to validate the simulation results.